Derecho a la salud y cuidados en el acceso a medicamentos antirretrovirales: el reclamo de las mujeres según archivos del Estado argentino durante la crisis del año 2002 - Colautti, Marisel Andrea (Anuario de Historia de América Latina, 2023)
In situations where the right to health is at risk of being violated, women generate care strategies. The theoretical approach focuses on public policies with a rights approach, specifically the right to health in times of crisis and the role of women in claiming the State to access antiretroviral drugs (ARV). This work aims to document progress and challenges in relation to the exercise of the right to health by a particularly vulnerable population and reveal the empowerment of women in a historical context. So, according to the State archives during the 2002 crisis, the question is: what characteristics did women claim for access to ARVs have beyond their serological condition? The objective is to describe the claim of women for access to ARV drugs according to archives of the Argentine State in the framework of the 2002 crisis. As a source of information, records of ARV purchases by the National Ministry of Health and semi-structured interviews with key informants were used. The categories were: civil society claim for the right to health, visibility in the media and communication modality with representatives of the State. The characterization carried out is adjusted to the sources of information used and this is recognized as a limitation of the work, however, the value of the archive that shows the interventions carried out by women as a self-care strategy or in their role as caregivers is highlighted. to access medications. Characteristics of programmatic vulnerability are observed. Women show great power of struggle and empowerment, taking to the streets to expand their rights over the care of their bodies, pursuing a comprehensive view of health.
Keywords: Gender; Care; HIV-AIDS; Vulnerability; Antiretrovirals; Argentina